2009
DOI: 10.1111/j.1740-0929.2008.00620.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemato‐biochemical changes, disease incidence and live weight gain in individual versus group reared calves fed on different levels of milk and skim milk

Abstract: A 2 x 3 factorial design was used to study the impact of rearing systems, individual (I) versus group (G) and different levels of milk/skim milk feeding (F1, F2 and F3) on hemato-biochemical profile, disease incidence and average daily gain of crossbred (Bos indicus x Bos taurus) calves. Six calves were taken in each group on the basis of their birth weight and housed in individual (2.20 x 1.16 m(2)/calf) or in group pens (2.20 x 1.03 m(2)/calf). After 3 days of colostrum feeding, calves were allocated to one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
3
16
1
Order By: Relevance
“…Some previous studies also found higher weight gain in grouped calves (Warnick et al, 1977;Babu et al, 2004;Babu et al, 2009), but others did not (Broom and Leaver, 1978;Purcell and Arave, 1991;Hänninen et al, 2003;Phillips, 2004). Most published studies on paired calves did not show a weight advantage over single-housed calves (Chua et al, 2002;De Paula Vieira et al, 2010;.…”
Section: Effect Of 4 D With Mother and Group Housing On Weight Of Calvesmentioning
confidence: 83%
See 2 more Smart Citations
“…Some previous studies also found higher weight gain in grouped calves (Warnick et al, 1977;Babu et al, 2004;Babu et al, 2009), but others did not (Broom and Leaver, 1978;Purcell and Arave, 1991;Hänninen et al, 2003;Phillips, 2004). Most published studies on paired calves did not show a weight advantage over single-housed calves (Chua et al, 2002;De Paula Vieira et al, 2010;.…”
Section: Effect Of 4 D With Mother and Group Housing On Weight Of Calvesmentioning
confidence: 83%
“…Also, the failure of some of the studies to find significant differences may be due to small sample sizes in relation to the large interindividual variability. We checked 12 studies that provided the average BW of the grouped or paired versus individually housed calves (Warnick et al, 1977;Broom and Leaver, 1978;Purcell and Arave, 1991;Chua et al, 2002;Hänninen et al, 2003;Babu et al, 2004;Phillips, 2004;Babu et al, 2009;De Paula Vieira et al, 2010;Jensen et al, 2015). In 11 of the 12 studies (all except Phillips, 2004), the overall average BW of grouped or paired calves were higher numerically.…”
Section: Effect Of 4 D With Mother and Group Housing On Weight Of Calvesmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, respiratory diseases and diarrhea were reported to occur more frequently in group-housed veal calves [8]. On the contrary, Babu et al [9] reported that rearing calves in a group resulted in a lower disease incidence. In other cases, health outcomes were similar between different housing systems [10].…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistent results were reported in previous research in which de Paula Vieira et al (2012) found no significant difference in the weight gain for calves between paired and single-housed calves. Babu et al (2009) observed a higher weight gain in grouped calves compared with calves kept individually. Our results agreed with several published studies, suggesting that paired calves do not show a weight advantage over single-housed calves (Chua et al 2002;de Paula Vieira et al 2010;Duve and Jensen 2012).…”
Section: Discussionmentioning
confidence: 82%